(untitled) (Journal of Hama University, 2022)
The study aimed to identify level of organizational confidence of nursing staff and to determine the relationship between organizational confidence and the organizational commitment of the nursing staff at Tishreen University Hospital in Lattakia city. The sample consisted of (200) nurses working at Tishreen University Hospital, who were present during the data collection period (convenience sample). The researcher used a questionnaire to assess organizational confidence, which was used by the researcher Khwain (2015) in her study on organizational confidence, and a questionnaire to assess organizational commitment that was used by researcher Salman (2013) in his assess of the organizational commitment, to collect data related to the study, and after the data were unpacking, it was statistically processed and tabulated using the statistical program SPSS version (20). The most important results of the study were: The level of organizational confidence of the nursing staff (the study sample) as a whole was average, and the level of organizational commitment of the nursing staff (the study sample) as a whole was moderate, with a strong and statistically significant relationship between organizational confidence and organizational commitment.